Uniform metric spaces, annular quasiconvexity and pointed tangent spaces - Herron, David A. (MATHEMATICA SCANDINAVICA, 2011)
We establish Väisälä's tangent space characterization for uniformity in the doubling metric space setting. We present similar results for other geometric properties.